2018
DOI: 10.1182/blood-2018-99-119249
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Flow Cytometry and Functional Imaging for Monitoring of Residual Disease in Myeloma

Abstract: Introduction The iliac crest is the usual sampling site for minimal residual disease (MRD) monitoring in Multiple Myeloma (MM). However, the disease distribution in the bone marrow (BM) is often heterogeneous. Functional imaging can be used to complement MRD detection at a single site, thereby accounting for asymmetrically distributed disease. Diffusion weighted MRI with background suppression (DWIBS) is a novel functional imaging method that can detect disease in a higher proportion of newly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…In the large FL, we identified a clone, which shared a “KRASGly12Val” with one of the baseline clones but presented with 65 new missense mutations that were not detectable at baseline despite deep multi-region sequencing. In the iliac crest sample, we found an additional resistant clone, which was also not detectable at baseline, and presented with another site-unique clonal KRAS mutation [ 49 ]. This observation highlights that even in MRD-negative patients, multiple spatially separated clones can survive.…”
Section: Impact Of Heterogeneity On Treatment Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the large FL, we identified a clone, which shared a “KRASGly12Val” with one of the baseline clones but presented with 65 new missense mutations that were not detectable at baseline despite deep multi-region sequencing. In the iliac crest sample, we found an additional resistant clone, which was also not detectable at baseline, and presented with another site-unique clonal KRAS mutation [ 49 ]. This observation highlights that even in MRD-negative patients, multiple spatially separated clones can survive.…”
Section: Impact Of Heterogeneity On Treatment Strategiesmentioning
confidence: 99%
“…Our group and others have shown that functional whole-body imaging can be used to monitor residual disease in MM and improve conventional MRD diagnostics [ 49 , 55 ]. In our study, 24% of first-line MM patients presented with residual FLs in DWIBS and/or PET-CT at the onset of CR, and these lesions were associated with short progression-free survival [ 49 ]. Although DWIBS is more sensitive than PET-CT in this context, the two techniques are complementary because some residual FLs are only detectable in PET-CT [ 49 ].…”
Section: Overcoming Tumor Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…This limitation can be, at least partially, mitigated by the concomitant use of functional imaging with fluoro-2-deoxyglucose positron emission tomography (FDG-PET). The presence of focal areas of FDG uptake postinitial therapy has been associated with higher risk of relapse (Zamagni et al, 2011;Moreau et al, 2017;Rasche et al, 2019), including among patients who were "MRD negative" in bone marrow assessment Rasche et al, 2019) with sensitivity of 10 À4 to 10 À5 . Therefore, the combination of undetectable tumour cells in marrow by NGS or NGF and lack of FDG uptake in marrow or extramedullary sites will identify patients with the best outcomes post-initial therapy (Rasche et al, 2019) and should be required for experimental approaches with therapy discontinuation.…”
Section: Can Current Mrd Methods Provide a Reliable Assessment Of Resmentioning
confidence: 99%
“…The presence of focal areas of FDG uptake postinitial therapy has been associated with higher risk of relapse (Zamagni et al, 2011;Moreau et al, 2017;Rasche et al, 2019), including among patients who were "MRD negative" in bone marrow assessment Rasche et al, 2019) with sensitivity of 10 À4 to 10 À5 . Therefore, the combination of undetectable tumour cells in marrow by NGS or NGF and lack of FDG uptake in marrow or extramedullary sites will identify patients with the best outcomes post-initial therapy (Rasche et al, 2019) and should be required for experimental approaches with therapy discontinuation. Can be performed locally, few centres have implemented Sample shipped to central laboratory from any site Required sample 2 9 10 7 nucleated cells Up to 20 µg of DNA (~3 9 10 6 nucleated cells) Can be performed in stored samples No Yes Limit of detection 2 9 10 À6 (20 events) 6Á8 9 10 À7 Limit of quantification 5 9 10 À6 (50 events) 1Á8 9 10 À6 FDA cleared No Yes FDA, US Food and Drug Administration; MM, multiple myeloma; MRD, minimal residual disease…”
Section: Can Current Mrd Methods Provide a Reliable Assessment Of Resmentioning
confidence: 99%